Why the Proximal Splenic Artery Approach is the Ideal Approach for Laparoscopic Suprapancreatic Lymph Node Dissection in Advanced Gastric Cancer? A Large-Scale Vascular-Anatomical-Based Study. Issue 18 (May 2015) - Chen, Rui-Fu; Huang, Chang-Ming; Chen, Qi-Yue; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Qi, Peng
<x xml:space="preserve">Abstract</x> Abstract Laparoscopic gastrectomy with D2 lymph node (LN) dissection has not yet been widely adopted for advanced gastric cancer because it is technically complicated. Due to the high suprapancreatic lymph nodes metastasis rate (LMR) and the various vascular anatomies, the suprapancreatic LN dissection is a crucial and demanding procedure for radical resection of gastric cancer. To explore the anatomical basis of the proximal splenic artery (SA) approach for laparoscopic suprapancreatic LN dissection and its application in advanced gastric cancer. Laparoscopic suprapancreatic LN dissections were performed in 1551 consecutive advanced gastric cancer patients between June 2007 and November 2013. A total of 994 consecutive patients since January 2011 were selected to compare the clinicopathological characteristics and surgical outcomes between the conventional approach group (330) and the proximal SA approach group (664). In the proximal SA approach, the No. 11p LNs are dissected first, followed by the Nos. 9, 7, and 8a LNs; dissection of the Nos. 5 and 12a LNs is performed last. In the suprapancreatic arteries, the proximal SA had the lowest anatomic variation rate (P < 0.05, each) and maximum diameter (P < 0.05, each) compared with the common hepatic artery (CHA), left gastric artery (LGA), right gastric artery (RGA), and gastroduodenal artery (GDA). In addition, the proximal SA was located closer to the suprapancreatic border than the CHA (P = 0.000). The No. 11p LMR was lower than the Nos. 9, 7, 8a, 5, and 12a LMR (P < 0.01, each). Compared with the conventional approach, the proximal SA approach was associated with less blood loss (P < 0.05), significantly more retrieved total LNs and suprapancreatic LNs (P < 0.01, each). The proximal SA exhibits the most constant and maximum diameter, is located closer to the suprapancreatic border, and exhibits the lowest LMR; therefore, the proximal SA approach is the ideal approach for laparoscopic suprapancreatic LN dissection in advanced gastric cancer.